Efforts to Improve Students' Self Esteem Through Group Guidance Services with the Problem Based Learning Method - Harahap, Masdalifah (Universitas Negeri Medan, 2025)
This study aims to improve the self-esteem of class VIII-2 students of SMP Negeri 5 Percut Sei Tuan through group guidance services with the Problem Based Learning (PBL) method. This type of research is Guidance and Counseling Action Research (PTBK) which is conducted in two cycles, each with two meetings. The subjects of the study were five students who had low self-esteem based on the results of the questionnaire. The results showed that there was an increase in the average self-esteem score from 61% (pre-test) to 67% (post-test I) and 80% (post-test II). This increase reflects the effectiveness of group guidance services with the PBL method in improving students' self-esteem. Thus, this service is recommended to be widely applied in guidance and counseling in schools.